Cover Feature: Altering Charges on Heterobimetallic Transition‐Metal Carbonyl Clusters (Chem. Eur. J. 54/2020). Issue 54 (11th September 2020) - Unkrig, Wiebke; Kloiber, Konstantin; Butschke, Burkhard; Kratzert, Daniel; Krossing, Ingo
Abstract : Anything is possible ! The cover depicts a scenario in ancient Egypt, with two construction masters considering possibilities for pyramids and invent a new method using [M(CO)6 ] – and Ag + as building blocks for pyramids, columns, and arches. Even an impressive bipyramid didn't discourage them. The [M(CO)6 ]‐fragments serve as ligands in the obtained [Ag m M(CO)6 n ] x ‐clusters (M=Nb, Ta; m =1, 2, 6; n =2, 3, 4, 5; x =1–, 1+, 2+), DFT based AIM calculations were performed to provide an understanding of the bonding situation and the cores of the cations were interpreted as superatoms. More information can be found in the Full Paper by I. Krossing et al. on page 12373 .